Les relations militaires entre l'Hispanie et la Maurétanie Tingitane à la fin du Ier siècle - Gwladys Bernard; Michel Christol (Mélanges de la Casa de Velázquez)
Tacitus's Histories is one of the main sources on the political crisis that blew up on the death of Nero in 68 AD. His account furnishes numerous details of the positions taken up by the North African provinces during this troubled period. The Mauritanians in particular are presented as a homogeneous group of procuratorian provinces subject to the decisions of powerful neighbours. A comparison of this sweeping judgement with the information supplied by epi-graphic documents- in this case military papers and soldiers' epitaphs- serves to qualify that view. In fact the army of Africa had no say in the choice of each of the Mauritanian provinces, which presented different features and political orientations. An examination of the origins of the troops making up the army of Mauritania Tingitana highlights the importance of recruitment in Hispania and the frequency with which units passed through the Iberian Peninsula.